Pregnancy Outcome in Early versus Late Onset Preeclampsia - Shrestha, Junu; Subedi, Anjali; Gauchan, Eva; Shrestha, Aashika; Pandey, Chandani (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To determine the pregnancy outcome of early and late onset preeclampsia. Methods: This was a cross sectional analytical study conducted in the department of Obstetrics and Gynaecology, Manipal Teaching Hospital from July to October 2021. All cases of preeclampsia diagnosed according to International Society of Study of Hypertension in Pregnancy 2018, were included. Early and late onset preeclampsia cut-off used was 34 weeks. Preeclampsia diagnosed before 34 were classified as early onset and after 34 weeks as late onset preeclampsia. Maternal and perinatal outcomes were analyzed using Statistical Package for Social Sciences version 21. Results: The prevalence of early onset and late onset preeclampsia were 4.3% and 8.3% of all deliveries. Early to late onset preeclampsia were 1:2. Renal involvement, placental abruption, IUGR, low birth weight, low Apgar and perinatal morbidity were significantly more in early onset; pre-term labor and use of MgSO4 and antihypertensives were also more in early onset. Conclusion: Late onset preeclampsia was more common than early onset preeclampsia but the maternal and perinatal outcome were poor for early onset as compared to late onset preeclampsia.